A novel thromboxane A2 receptor N42S variant results in reduced surface expression and platelet dysfunction - Nisar, Shaista P.; Lordkipanidzé, Marie; Jones, Matthew L.; Dawood, Ban B.; Murden, Sherina; Cunningham, Margaret R.; Mumford, Andrew D.; Wilde, Jonathan T.; Watson, Steve P.; Mundell, Stuart J.; Lowe, Gillian C.; the UK GAPP Study Group; on behalf of (Thrombosis and Haemostasis, 2014)
A small number of thromboxane receptor variants have been described in patients with a bleeding history that result in platelet dysfunction. We have identified a patient with a history of significant bleeding, who expresses a novel heterozygous thromboxane receptor variant that predicts an asparagine to serine substitution (N42S). This asparagine is conserved across all class A GPCRs, suggesting a vital role for receptor structure and function. We investigated the functional consequences of the TP receptor heterozygous N42S substitution by performing platelet function studies on platelet-rich plasma taken from the patient and healthy controls. We investigated the N42S mutation by expressing the wild-type (WT) and mutant receptor in human embryonic kidney (HEK) cells. Aggregation studies showed an ablation of arachidonic acid responses in the patient, whilst there was right-ward shift of the U46619 concentration response curve (CRC). Thromboxane generation was unaffected. Calcium mobilisation studies in cells lines showed a rightward shift of the U46619 CRC in N42S–expressing cells compared to WT. Radioligand binding studies revealed a reduction in BMax in platelets taken from the patient and in N42S–expressing cells, whilst cell studies confirmed poor surface expression. We have identified a novel thromboxane receptor variant, N42S, which results in platelet dysfunction due to reduced surface expression. It is associated with a significant bleeding history in the patient in whom it was identified. This is the first description of a naturally occurring variant that results in the substitution of this highly conserved residue and confirms the importance of this residue for correct GPCR function.
Keywords: Inherited / acquired platelet disorders; gene mutations; receptors; platelet pharmacology; platelet pathology / inherited; acquired